1998
DOI: 10.1152/ajplung.1998.274.6.l1024
|View full text |Cite
|
Sign up to set email alerts
|

cAMP protects endothelial barrier function independent of inhibiting MLC20-dependent tension development

Abstract: Exposure of cultured human umbilical vein endothelial cells to the cAMP agonists theophylline and forskolin decreased constitutive isometric tension of a confluent monolayer inoculated on a collagen membrane, but it did not prevent increased tension in cells exposed to thrombin. The inability of cAMP agonists to prevent tension development correlated with an inability of cAMP stimulation to prevent increased 20-kDa myosin light chain (MLC20) phosphorylation in response to thrombin. Although cAMP did not preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 15 publications
1
56
1
Order By: Relevance
“…31,33,34 In fibroblasts, it has been shown that LPA lowers cAMP levels, probably by coupling G I proteins to an LPA receptor, 35 and cAMP is known to improve endothelial barrier function. [25][26][27] However, LPA did not significantly lower cAMP levels in ECs, excluding the possibility of a reduction in cAMP levels as the mechanism of LPA action.…”
Section: Discussionmentioning
confidence: 77%
“…31,33,34 In fibroblasts, it has been shown that LPA lowers cAMP levels, probably by coupling G I proteins to an LPA receptor, 35 and cAMP is known to improve endothelial barrier function. [25][26][27] However, LPA did not significantly lower cAMP levels in ECs, excluding the possibility of a reduction in cAMP levels as the mechanism of LPA action.…”
Section: Discussionmentioning
confidence: 77%
“…It also may provide a molecular basis for gravity sensing (Ingber, 1999;Yoder et al, 2001) and control of circadian rhythmicity (Shweiki, 1999) in both animals and plants. In addition, tensegrity may help to explain why cellular components that are not directly involved in actomyosin-based tension generation, such as microtubules, intermediate filaments and ECM, can contribute significantly to contractile function in various cell types, including cardiac myocytes, vascular smooth muscle and skeletal muscle (Northover and Northover, 1993;Tsutsui et al, 1993;Lee et al, 1997;Tagawa et al, 1997;D'Angelo et al, 1997;Eckes et al, 1998;Gillis, 1999;Wang and Stamenovic, 2000;Keller et al, 2001;Balogh et al, 2002;Loufrani et al, 2002) as well as to control of permeability barrier function in endothelia (Moy et al, 1998).…”
Section: Tissue Morphogenesis In Contextmentioning
confidence: 99%
“…Junctional integrity is regulated by cAMP, and stimuli such as prostacyclins that elevate the level of cAMP inhibit cell permeability (Moy et al, 1998). It was anticipated that protein kinase A (PKA) mediates this effect, but the findings that Rap1 is involved in the formation of E-cadherin-based junctions and that cAMP directly activates the RapGEF Epac prompted several groups to examine whether Epac and Rap1 mediate the cAMP-induced effect.…”
Section: Rap1 and The Regulation Of Ve-cadherinmentioning
confidence: 99%